MicroRNA expression pattern differs depending on endometriosis lesion type†. Issue 5 (29th January 2018) - Haikalis, Maria E; Wessels, Jocelyn M; Leyland, Nicholas A; Agarwal, Sanjay K; Foster, Warren G
Abstract: MicroRNA (miRNA), noncoding segments of RNA involved in post-transcriptional regulation of protein expression are differentially expressed in eutopic endometrium of women with and without endometriosis compared to endometriotic lesions. However, endometriotic lesion types are known to be biochemically distinct and therefore hypothesized that miRNAs are differentially expressed in endometriomas compared to peritoneal and deep-infiltrating lesions. Therefore, endometrial biopsies and ectopic implants from women (n = 38) undergoing laparoscopic surgery for chronic pelvic pain were collected. Samples of endometriomas, peritoneal or deep-infiltrating lesions were selected from our tissue bank for study participants who exclusively had only one lesion type noted on their surgical report. Quantitative real-time polymerase chain reaction for miR-9, miR-21, miR-424, miR-10a, miR-10b, and miR-204 was performed. miR-204 expression was significantly lower ( P = 0.0016) in the eutopic endometrium of women with endometriosis compared to controls. Relative expression of miR-21, miR-424, and miR-10b differed significantly ( P < 0.05) across endometriotic lesion types. Finally, all miRNAs isolated from endometriomas, peritoneal and deep-infiltrating lesions studied were differentially expressed compared to matched eutopic endometrium samples. We therefore conclude that miRNA expression in the eutopic endometrium from women with endometriosis differs from symptomatic controls. Moreover, miRNA expression pattern is dependent on the endometriotic lesion type studied. We suggest that identification of different miRNA expression patterns for endometriomas, peritoneal and deep-infiltrating lesions could contribute to individualized patient care for women with endometriosis. Summary Sentence: MicroRNAs are differentially expressed in endometriomas, peritoneal and deep infiltration endometriotic lesions, suggesting that endometriotic lesions from different anatomical sites are biochemically distinct.